Numerical Study of a Dual-Mode Optical Sensor for Temperature and Refractive Index Sensing with Enhanced Temperature Range - Muhammad Favad Qadir; Muhammad Zakwan; Saleem Shahid; Ahsan Sarwar Rana; Muhammad Mahmood Ali; Wolfgang Bösch (Sensors)
This study presents a photonic integrated optical sensor based on a dual-polarization microring resonator with angular gratings on a silicon-on-insulator (SOI) waveguide, enabling simultaneous and precise refractive index (RI) and temperature measurements. Due to the distinct energy distributions for transverse electric (<semantics>TE</semantics>) and transverse magnetic (<semantics>TM</semantics>) modes in SOI waveguides, these modes show distinct sensitivity responses to the variation in ambient RI and temperature. Simultaneous measurements of both temperature and RI are enabled by exciting both these transverse modes in the microring resonator structure. Furthermore, incorporating angular gratings into the microring resonator’s inner sidewall extends the temperature measurement range by mitigating free spectral range limitations. This work presents a novel approach to dual-polarization microring resonators with angular gratings, offering an enhanced temperature measurement range and detection limit in optical sensing applications requiring an extended temperature range. The proposed structure is able to yield a simulated temperature measurement range of approximately 35 nm with a detection limit as low as <semantics>2.99×10−5</semantics>. The achieved temperature sensitivity is 334 pm/°C and RI sensitivity is 13.33 nm/RIU for the <semantics>TE0</semantics> mode, while the <semantics>TM0</semantics> mode exhibits a temperature sensitivity of 260 pm/°C and an RI sensitivity of 76.66 nm/RIU.